The influence of primary soil tillage methods and foliar nutrient provision on the growth, yield, and associated traits of winter barley (Hordeum vulgare L.) - Assefa Bogale, Amare; Percze, Attila (Acta Agraria Debreceniensis, 2025)
Sustainable agricultural practices are vital for ensuring global food security. Factors such as soil, weather, and agronomic practices, including nutrient supply and tillage systems, play key roles in sustainable crop production. A field experiment at the Hungarian University of Agriculture and Life Sciences in Godollo, Hungary, assessed the impact of primary soil tillage methods and foliar nutrient supplementation on winter barley yield and traits. Using a split-plot design with three replications, the study examined four nutrient treatment (control, Bio-cereal, bio-algae, and MgSMnZn Blend) and two tillage methods (plowing and cultivator). The obtained results indicated no significant influence of tillage treatments on SPAD value, leaf area index (LAI), plant height, or spike length. However, nutrient treatments significantly (P